ANTIHYPERTENSIVE PRESCRIBING PATTERNS AND JNC-8 GUIDELINE COMPLIANCE IN A SOUTHERN NIGERIA HEALTHCARE SETTING - Nwosu, Ifeanyi Chukwudi; Okonjo, Ezinne Patricia (Research Journal of Nursing and Clinical Practice, 2024)
Background: Hypertension is a significant public health concern globally, particularly in Nigeria, where its prevalence is rising sporadically. Effective management of hypertension requires adherence to evidence based guidelines, such as those provided by the Eighth Joint National Committee (JNC-8). This study aimed to evaluate the prescribing pattern of hypertensive medications and their adherence to JNC-8 guidelines in a tertiary care hospital in Southern Nigeria. Methods: A retrospective study was conducted on 194 prescriptions for a period of 6 months (October,2023 to March,2024) from two cardiologists and four general practitioners. Baseline characteristics, including age distribution and blood pressure readings, were assessed. Medication classes prescribed for hypertension were categorized, and adherence to JNC-8 guidelines was evaluated. Results: The mean age of the study population was 54.7 years, with a majority falling into the age groups of 41-60 and >60. The mean systolic and diastolic blood pressure readings were 151 mmHg and 94.6 mmHg, respectively. While 62.89% of the subjects had controlled blood pressure according to JNC-8 guidelines, 37.11% belonged to the uncontrolled group (blood pressure >140/90 mmHg). The gender distribution showed a slight predominance of males (52%) over females (45%). The most commonly prescribed antihypertensive medication classes were CCBs (72.16%), BBs (58.76%), diuretics (45.26%) and ARBs (42.24%). Adherence to JNC-8 guidelines was higher among prescriptions with controlled blood pressure (group 2) compared to uncontrolled (group 1) Conclusion: The factors affecting prescribing patterns and guideline adherence in hypertension management include the complexity of treatment decisions, variations in physician experience and knowledge, and challenges such as managing resistant hypertension and addressing patientspecific factors. While a significant proportion of patients achieve controlled blood pressure levels, deviations from guideline recommendations indicate opportunities for improvement. Addressing these factors through targeted interventions aimed at enhancing guideline adherence and optimizing prescribing practices is crucial for improving hypertension management outcomes in Southern Nigeria and reducing the burden of cardiovascular diseases in the region.